Efektivitas Model Pembelajaran Kooperatif Tipe Teams Games Tournaments (TGT) Terhadap Hasil Belajar Matematika Siswa Kelas VII SMP Negeri 3 Kempo - Yoniar Puspita Dewi; Nyoman Sridana; Baidowi Baidowi; Sripatmi Sripatmi (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This research aims to determine the effectiveness of the Teams Games Tournaments (TGT) cooperative learning model on the learning outcomes of VII grade students SMPN 3 Kempo academic year 2020/2021 on the material algebraic form. The type of research is pre-experimental research with one shot case study design. The research was conducted in 4 meeting for using the TGT cooperative learning and 1 meeting for the implementation of the posttest. The sample is done by purposive sampling technique, the sample was class VII-A as the experimental class which is using the TGT cooperative learning. Data collection using observation and test techniques. Instruments include: observation sheets and learning outcomes tests. The learning outcome data is used to determine how far the students understand the material being taught and the observation data is used to determine the quality of the teaching and learning process which is analyzed descriptively. The research indicator is model TGT cooperative learning, effective if the students’ learning with a classical learning completeness percentage ≥ 85%. Based on the results obtained 16 students who had completed their studies or equal to 88.89% and 2 students who did not complete their studies or 11.11%. The results of observations teacher activities obtained 85% with good criteria, and observations students activities obtained 80% with active criteria. Based on the research results, the cooperative learning model type Teams Games Tournaments (TGT) is effective on the learning students outcomes.